Efektifitas Metode Qira’ati dalam Pembelajaran Membaca Al-Qur’an Bagi Anak Usia Dini - Imam Mashudi Latif (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
Al-Qur'an learning using the Qira’ati method is very easy and practical to apply to young children. At an early age is the golden age or golden period where children will be responsive and can quickly read the Qur'an properly and correctly. This paper aims to describe the effectiveness of the Qira'ati method in learning to read the Qur'an for Early Childhood, which is examined through several literatures related to the subject, using qualitative descriptive analysis. In conclusion, the Qira'ati method is very suitable and very effective to improve learning to read the Qur'an for early childhood because the process is very easy, on the other hand children at an early age are at the golden age or golden stage of development where children will respond quickly to what their teachers teach. Children can easily pronounce hijaiyah letters properly and correctly